2017
DOI: 10.1007/s10834-017-9551-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Hardship on Single Parents: An Exploration of the Journey From Social Distress to Seeking Help

Abstract: Single parent families are at high risk of financial hardship which may impact on psychological wellbeing. This study explored the impact of financial hardship on wellbeing on 15 single parents. Semi-structured interviews were conducted and analysed using constructivist thematic analysis. Participants described food and fuel poverty, and the need to make sacrifices to ensure that children’s basic needs were met. In some cases, participants went without food and struggled to pay bills. Isolation, anxiety, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 36 publications
6
67
0
4
Order By: Relevance
“…When neither marriage nor cohabitation occurs before or after childbearing, another variant of the family occurs, referred to as parenthood without partnership . There is a robust literature on single parenthood among the highly disadvantaged (Damaske, Bratter, & Frech, 2017; Meier, Musick, Flood, & Dunifon, 2016; Stack & Meredith, 2018), though not on the creation of kinship networks. Naming practices (both first names and surnames) were often used to signify and reinforce paternal obligations, if a father was present.…”
Section: Methodsmentioning
confidence: 99%
“…When neither marriage nor cohabitation occurs before or after childbearing, another variant of the family occurs, referred to as parenthood without partnership . There is a robust literature on single parenthood among the highly disadvantaged (Damaske, Bratter, & Frech, 2017; Meier, Musick, Flood, & Dunifon, 2016; Stack & Meredith, 2018), though not on the creation of kinship networks. Naming practices (both first names and surnames) were often used to signify and reinforce paternal obligations, if a father was present.…”
Section: Methodsmentioning
confidence: 99%
“…These workers experience high levels of work-family conflict and insecurity due to severe competing demands on their time and consequently experience lower health outcomes. Stack and Meredith (2018) reported that single working parents experienced grinding poverty, psychological distress, and anxiety, even when employed on a full-time basis, because of their low hourly rates of pay. According to Danziger and Waters Booth (2008), although the non-work needs of low SES workers echo those of higher SES workers, they are less likely to be accommodated by employers due to the casual nature of the work.…”
Section: Impact Of Social-economic Statusmentioning
confidence: 99%
“…With the help of making budget, parent achieve an idea regarding the income and expenditure so that they can also make balance between income and expenditure. Single parents need to save and invest their monetary resources for emergencies and future safety (Stack & Meredith, 2018). iv.…”
Section: IIImentioning
confidence: 99%